Age Verification Regulation in Social Media Platform Usage: Preventive Measures Against Online Child Sexual Violence - Jamaludin, Ahmad (Jurnal Bina Mulia Hukum, 2024)
The escalation of internet use in various age groups has resulted in an increase in the number of social media users from year to year, until at the beginning of 2023 there were 212.9 million internet users and 167 million social media users, equivalent to 60.4% of the total population, it is also known that around 87% of children in Indonesia have been introduced to social media before turning 13 years old. With easy access to the internet, perpetrators of sexual violence are increasingly adapting to exploit children's vulnerability, thus changing the dimensions of sexual violence that are increasingly directed at children. This phenomenon has made several developed countries adapt by implementing various approaches to prevent children from becoming victims of sexual violence in cyberspace. This research aims to obtain a complete picture of sexual violence against children facilitated by social media platforms, and find alternative policies to limit access to protect children from a series of vulnerabilities that can result in sexual violence in cyberspace. The research method used in this research is normative juridical. The results of the study found that if today's easy access to social media has made children more vulnerable to becoming victims of sexual violence in cyberspace, prevention with a criminal law and telematics approach should be carried out to prevent children from perpetrators of sexual violence. Indonesia has actually taken a proactive policy with the enactment of the Personal Data Protection Law, but it has not regulated provisions related to age limits and rules that require strict application of age verification for children accessing social media.